2015
DOI: 10.2217/pgs.15.71
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin and Leptin Gene Polymorphisms in Patients With Post-Transplant Diabetes Mellitus

Abstract: The results of our study suggest an association between the leptin rs2167270 gene A allele and PTDM. Original submitted 27 February 2015; Revision submitted 22 May 2015.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 36 publications
2
27
1
Order By: Relevance
“…A study by Romanowski et al47 conducted on 169 Caucasian patients (23 with PTDM) revealed an association between IL-17F SNP (rs763780) and PTDM. No significance was found for IL-17A polymorphism (rs2275913) and 2 other evaluated SNPs of IL-17F (rs11465553 and rs2397084) 47…”
Section: Genetic Polymorphisms and Risk Of Diabetes Mellitusmentioning
confidence: 99%
“…A study by Romanowski et al47 conducted on 169 Caucasian patients (23 with PTDM) revealed an association between IL-17F SNP (rs763780) and PTDM. No significance was found for IL-17A polymorphism (rs2275913) and 2 other evaluated SNPs of IL-17F (rs11465553 and rs2397084) 47…”
Section: Genetic Polymorphisms and Risk Of Diabetes Mellitusmentioning
confidence: 99%
“…Leptin gene polymorphisms are associated with obesity, insulin resistance, and diabetes mellitus, as demonstrated in a study by (Romanowski et al, 2015). The association of polymorphisms in the leptin gene with GDM is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to regulating appetite and metabolism, this adipokine is important in insulin secretion (Romanowski et al, 2015). Insulin resistance is an important feature of gestational diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, numerous other genetic studies for PTDM have been conducted in renal transplant recipients, and nearly 50 loci have been established as suspected loci (Table 4) [7][8][9][10]13,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41]. Polymorphisms in AIPOQ, CAPN10, CDKAL1, CDKN2A/B, HHEX, KCN11, KCNQ1, SLC30A8, and TCFL2 are known to be associated with T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…Leptin (LEP) and leptin receptor (LEPR) gene polymorphisms have been reported to be associated with insulin resistance, obesity, and diabetes mellitus [11,12]. However, only a few studies have evaluated the clinical impact of LEP and LEPR polymorphisms on the development of PTDM [13].…”
Section: Introductionmentioning
confidence: 99%